PENGARUH MODEL PEMBELAJARAN MUHIBBAH TERHADAP KESUKSESAN BELAJAR MAHASISWA - Moh Ali; A. Kumedi Ja'far (Almarhalah, 2023)
ABSTRACTThe success of the teaching and learning process is the ideal of  the academic community regardless of  their position. This success can be  measured to the extent to wich each teacher is ebel to present teaching material properly and easily digensted by student  as well,In edition to the ability and goog anderstanding of the subject they have, mastery of learning matterials, learning strategies ang edition to a sense of empathy, as wel as a wealth of ideas in the teaching –learning procces. One the Muhibbah  lecture model is  an educational  model that focuses  on how students enjoy  and have fun   interacting  with their lecturers. Discussion , dialogue, visit to ech other, exemplay behavior ang maintaining  togederness, unity and full of intimacy. Keywords: Good Lecture  model Muhibbah.